Lions, Hares, and Donkeys: Illustrating Regal Traits in Johannes Magnus’ Historia de omnibus Gothorum Sueonumque regibus (1554) - Nilsson, Astrid M. H. M. H. (Literatūra, 2018)
[full article, abstract in English; abstract in Lithuanian] Johannes Magnus (1488–1544) was the last Catholic archbishop of Uppsala to hold residence in Sweden. He was also an historian and wrote a major work on Swedish history, the Historia de omnibus Gothorum Sueonumque regibus, which was published posthumously in Rome in 1554. The work eventually became the ideological foundation for Swedish patriotism in the 17th century. The Historia de regibus places a very strong focus on the monarchs: the work is actually arranged as a series of royal biographies. Imagery is rare in Johannes Magnus’ work, which makes it especially striking when it does occur and also suggests that it is important. He sometimes refers to the animal kingdom to illustrate character traits and actions of the monarchs. In this paper, this animal imagery is analyzed and contextualized in order to explain its implications.